Bacteriophages of Leuconostoc, Oenococcus, and Weissella - Kot, Witold; Neve, Horst; Heller, Knut J.; Vogensen, Finn K. (Frontiers in Microbiology, 2014)
Leuconostoc (Ln.), Weissella and Oenococcus form a group of related genera of lactic acid bacteria, which once all shared the name Leuconostoc. They are associated with plants, fermented vegetable products, raw milk, dairy products, meat and fish. Most of industrially relevant Leuconostoc strains can be classified as either Ln. mesenteroides or Ln. pseudomesenteroides. They are important flavor producers in dairy fermentations and they initiate nearly all vegetable fermentations. Therefore bacteriophages attacking Leuconostoc strains may negatively influence the production process. Bacteriophages attacking Leuconostoc strains were first reported in 1946. Since then, the majority of described Leuconostoc phages was isolated from either dairy products or fermented vegetable products. Both lytic and temperate phages of Leuconostoc were reported. Most of Leuconostoc phages examined using electron microscopy belong to the Siphoviridae family and differ in morphological details. Hybridization and comparative genomic studies of Leuconostoc phages suggest that they can be divided into several groups, however overall diversity of Leuconostoc phages is much lower as compared to e.g. lactococcal phages. Several fully sequenced genomes of Leuconostoc phages have been deposited in public databases. Lytic phages of Leuconostoc can be divided into two host species-specific groups with similarly organized genomes that shared very low nucleotide similarity. Phages of dairy Leuconostoc have rather limited host-ranges. The receptor binding proteins of two lytic Ln. pseudomesenteroides phages have been identified. Molecular tools for detection of dairy Leuconostoc phages have been developed. The rather limited data on phages of Oenococcus and Weissella show that i) lysogeny seems to be abundant in Oenococcus strains, and ii) several phages infecting Weissella cibaria are also able to productively infect strains of other Weissella species and even strains of the genus Lactobacillus.